2021
DOI: 10.1002/jmri.27937
|View full text |Cite
|
Sign up to set email alerts
|

Improved Assessment of Longitudinal Spinal Cord Atrophy in Multiple Sclerosis Using a Registration‐Based Approach: Relevance for Clinical Studies

Abstract: Background Reliable measurements of cervical cord atrophy progression may be useful for monitoring neurodegeneration in multiple sclerosis (MS). Purpose To compare a new, registration‐based (Reg) method with two existing methods (active surface [AS] and propagation segmentation [PropSeg]) to measure cord atrophy changes over time in MS. Study Type Retrospective. Subjects Cohort I: Eight healthy controls (HC) and 28 MS patients enrolled at a single institution, and cohort II: 25 HC and 63 MS patients enrolled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It was demonstrated that progressing MS and RRMS patients had opposing effects on SC volume. They illustrated the drift towards larger cervical cord volumes in RRMS patients exclusively, which they interpreted as expansions owing to inflammation or edema that would disguise real atrophy [16][17] . SC atrophy appeared to be more pronounced than brain atrophy, indicating higher susceptibility towards pathogenic alterations in MS, as evidenced through a significantly deteriorated SC.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that progressing MS and RRMS patients had opposing effects on SC volume. They illustrated the drift towards larger cervical cord volumes in RRMS patients exclusively, which they interpreted as expansions owing to inflammation or edema that would disguise real atrophy [16][17] . SC atrophy appeared to be more pronounced than brain atrophy, indicating higher susceptibility towards pathogenic alterations in MS, as evidenced through a significantly deteriorated SC.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy controls showed changes in CSA of up to -0.7% over 2 years (difference between baseline and 2-year follow-up), which might be due to aging ( Papinutto et al, 2015 ), natural fluctuations, test-retest variability, or remaining effects of the scanner upgrade. Ultimately, this would limit the ability to detect subtle changes in CSA in diseases where expected effect sizes are rather small such as multiple sclerosis ( Prados et al, 2020 ;Valsasina et al, 2022 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Regarding technical limitations of this study, dedicated longitudinal methods for the assessment of SC atrophy rates should preferably be used in future studies. Recently developed registration-based methods for measuring longitudinal volume changes could increase reliability [34,41].…”
Section: Limitationsmentioning
confidence: 99%